DEPREMZEDE KAN ÖRNEKLERİNDE 14 BİYOKİMYASAL PARAMETREDE MEYDANA GELEN DEĞİŞİMLER - HACIBEKİROĞLU, Münire; BALCI, Huriye; KASIM, Aysel (Cerrahpaşa Medical Journal, 2019)
Background and Design.-Our objective is to determine whether the two Marmara earthquakes in 1999 have led to post-traumatic stress (Group 1), crush syndrome (Group 2), or changes in kidney functions (Group 3) and acute phase reactants (Group 4). We studied the cortisol levels for post-traumatic stress; the SGOT, SGPT, LDl-I, CK and K levels for crush syndrome; urea, creatinine, Beta-2-Microglobulin, and cystatin-C levels for kidney function; and CRP, transferrin, haptoglobin, and ceruloplasmin levels for acute phase reactants. Results and Conclusion.- The study covered blood samples from those who came for the three time (Group A; n: 76,Group B; n: 32,Group C; n: 14) at average 9-day intervals. Samples from 20 healthy volunteers were used as control group. Urea, creatinine, SGOT, SGPT, LDH, CK, K and cystatin-C levels were measured with a Hitachi-717 analyzer; Beta-2-Microglobulin and cortisol levels with a DPC immulite device; and CRP, haptoglobin, ceruloplasmin transferrin levels with a Behring Nephelometer. Further analysis revealed no significant subsequent changes in the parameters of the cases in Groups A, B, C, although a decrease was observed in all high values.